TANGGUNGJAWAB NOTARIS TERHADAP PEMBUATAN AKTA DENGAN NOMOR GANDA - Ni Kadek Yunia Permata Sari; I Made Hendra Wijaya (Jurnal Hukum Mahasiswa, 2021)
A notary is a public official who is authorized to make an authentic deed. In practice there can be problems with authentic deeds made by a notary due to negligence, lack of care/carelessness (prudence), one of the problems is the existence of double numbering. In making this deed, the deed number is made so that the authentic deeds are registered by the notary in sequence so that it can be easy to find and distinguish them from other deeds. The type of research used is normative legal research with a statutory approach and a concept approach. Sources of legal materials in this study consist of: primary, secondary, and tertiary. The technique of collecting legal materials is a literature study technique. The analysis of the legal materials collected in this study was carried out in a descriptive, interpretative, evaluative and argumentative analysis